Improved varietal technology for enhanced productivity in sorghum - Aruna, C; Madhusudhana, R; Bhat, B V; Umakanth, A V (Indian Farming, 2023)
Sorghum is a multipurpose crop that can be grown for a variety of uses like food, feed, forage and fuel, and is well adapted to different soil and weather conditions. There is distinct seasonal adaptation of grain sorghum cultivars and commodity-specific cultivars for green forage (rainfed single-cut, irrigated multi-cut), bioethanol production (sweet stalked sorghum) mark the clear-cut separate classes that exemplify the adaptation and diversity in sorghum as a crop. The research efforts over five decades have resulted in the release of more than 80 improved cultivars at the national level and more than 200 at state level with traits of high grain yield, biotic and abiotic resistance, fodder types, and sweet sorghum genotypes etc.